2015
DOI: 10.1002/lary.25310
|View full text |Cite
|
Sign up to set email alerts
|

Construct validity of cadaveric temporal bones for training and assessment in mastoidectomy

Abstract: N/A.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
28
0
2

Year Published

2017
2017
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 22 publications
(33 citation statements)
references
References 17 publications
3
28
0
2
Order By: Relevance
“…Our results for individual items are similar to those in the reports of Laeeq et al 11 and Awad et al 12 Other instruments, such as the Welling Scale and the one by Zirkle et al 13 have also been developed, and a review can be read in Sethia et al 7 . The checklists in the current work are similar to those of the Johns Hopkins assessment.…”
Section: Comparison With Other Studiessupporting
confidence: 89%
“…Our results for individual items are similar to those in the reports of Laeeq et al 11 and Awad et al 12 Other instruments, such as the Welling Scale and the one by Zirkle et al 13 have also been developed, and a review can be read in Sethia et al 7 . The checklists in the current work are similar to those of the Johns Hopkins assessment.…”
Section: Comparison With Other Studiessupporting
confidence: 89%
“…Fifty‐one studies were included in the review, of which 47 were full‐text original research articles and four were conference posters. The main characteristics of studies, including OCEBM and mean MERSQI scores are shown in Tables S2 – S5 (supporting information).…”
Section: Resultsmentioning
confidence: 99%
“…Various score‐based methods were also used, including procedure scores, global rating scale (GRS), OSATS (Objective Structured Assessment of Technical Skills in Surgery) and the GOALS (Global Operative Assessment of Laparoscopic Skills) scale. Seven of the 23 studies were RCTs and 16 were cohort studies. Of the seven RCTs, three compared cadaveric simulation with no simulation training, and four compared cadaveric simulation with low‐fidelity simulation.…”
Section: Resultsmentioning
confidence: 99%
“…Both of the scales use a list of evaluation items with ratings of one to five. Work by Laeeq et al 7 and Awad et al 8 show some validity evidence for that instrument but in only a small number of institutions.…”
Section: Previous Workmentioning
confidence: 94%